The effect of social media on consumer purchase behaviour in the mobile telephony industry in Zimbabwe - Forbes Makudza; Cleopatra Mugarisanwa; Shingirai Siziba (Dutch Journal of Finance and Management, 2020)
This paper examines the causal relationship between social media and consumer purchasing behaviour in the mobile telephony industry in Zimbabwe. The study was driven by a strong desire to convert social media usage into desirable purchase behaviour. Social media was examined using four variables namely, firm generated communication, user created communication, word of mouth and social media platform. The study results indicate that social media is a significant driver of consumer purchase intention. Consumer purchase behaviour is mainly driven by social media word of mouth, whilst firm generated content was found to be inversely related to purchase intention. User generated social media communication resulted in a moderately weak association with purchase behaviour, whilst an insignificant association was obtained between social media platform and consumer purchase intention. The results imply that social media is an effective tool but needs to be adapted so as to minimize generating content which distorts desirable consumer behaviour. The researchers therefore recommend a cautious social media campaign which generates more desirable viral content.
Keywords: 650; socialmedia; consumerbehaviour; purchaseintention; marketing; wordofmouth